Pengaruh Motivasi Terhadap Disiplin Kerja Karyawan Bagian Marketing PT. DM Cabang Pekanbaru - Nurmadania, Nurmadania; Risman, Risman (Eko dan Bisnis: Riau Economic and Business Review, 2024)
The purpose of this study was to determine the effect of motivation on the work discipline of employees in the marketing division of PT. DM Pekanbaru Branch. To achieve this goal, a study was conducted using a sample of 47 people, using the census method. Methods of data analysis using simple linear regression. Based on the test results on the motivation variable (X), the t-count is greater than the t-table (9.913 > 2.014). R2 of 0.686 (68.6%) explains that the motivational variable contributes to the influence of the work discipline of the employees of the Marketing Department of PT. DM Pekanbaru Branch of 68.6%. While the remaining 31.4% describes other independent variables not observed in this study. Recommendations that can be submitted It is expected that employees of PT. DM Pekanbaru Branch quickly adjusts to the work environment because this gets the lowest response from respondents.